Les récits des miracles d’Ignace de Loyola - Axelle Guillausseau (Mélanges de la Casa de Velázquez)
Focusing on hagiographic documents concerning Ignatius Loyola published in the kingdoms of France and Spain during the second half of the 16th century and the first half of the 17th, this article seeks to demonstrate several characteristic features of the new hagiography which emerged from the Catholic Reform. It does this by examining at once the redefinition of criteria for sainthood and the uses that were made of printing in the field of religion. Thus, the analyses cover the influence exerted on saintly writing by the idea of reform, and the spiritualisation of recitals of miracles as this relates to the didactic functions then attributed to them ; but they also address the linkage between national feeling and hagiography, which is revelatory at once of the Tridentine drive for devotional uniformity and of the reaffirmation of special votive forms.